Skrajne i pośrednie twory poprawności politycznej - Nowak, Maciej (Er(r)go. Teoria - Literatura - Kultura, 2005)
Maciej Nowak Extreme and Intermediary Forms of Political Correctness Nowak reads various implicit mechanisms of political correctness through Žižek’s and Nietzsche’s specific discussion of Christainity, Western worldview and its discontents. His theoretical considerations are coloured by examples from Polish and Anglosaxon culture and literature, as well as a vivid (nocturnal) reading of a lucrative Hollywood production The Independence Day.